Enhancing The Organization’s Character Through Pancasila Values In The Era Of Brittle, Anxiety, Non-Linear, Incomprehensive (Bani) - Alif Lukmanul Hakim (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
Improving organizational character is part of the maturation process of an organization, which is to respond to a reality that is happening. The background of this research explains the phenomenon of the rapid development of the times, as well as the aspects of the consequences of the development of the times. The BANI era is required to be able to learn and adapt quickly which requires a mature fundamental character. This research aims to explain the concepts of Pancasila as a foundation for improving character in an organization through the values contained therein. This research uses the literature method. The formal object in this research is the essence of the five precepts of Pancasila in relation to organizational character. Then the material object in this research is the improvement of character in the organization which is viewed from the normative and empirical aspects of an organization. This research shows that Pancasila becomes a basic value that can be used as a reference or guideline for an organization to improve the character of each stakeholder in it. The embedded values are also in line with the culture and character of the Indonesian nation.